The International Journal of Acoustics and Vibration 2022
DOI: 10.20855/ijav.2022.27.41876
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Deformation on Sound-Absorbing Performance Under Hydrostatic Pressure

Abstract: The sound-absorbing rubber coating is easy to deform under hydrostatic pressure, resulting in variation in acoustic properties. For improving the accuracy of the deformation of the sound-absorbing structure under hydrostatic pressure, four hyperelastic constitutive models of Mooney-Rivlin, Neo-Hookean, Yeoh and Arruda-Boyce were selected in fitting the tensile curve of the dumbbell specimen and the compressive curve of a cylindrical specimen. The comparison in their applicability and the accuracy showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…(a) Two-layer FGMs composite; (b) single-layer FGM is compounded with gradient cavities; (c) two-layer FGMs are compounded with gradient cavities 图 4 (网络版彩色)具有增强结构的抗压水声吸声结构. (a) 含钢隔 板增强结构的吸声材料在4.5 MPa下x方向的位移场图 [94] , Copyright © 2022, Acoustic Society of America; (b) 通过铝制圆筒增强柱形空 腔抗压性能的吸声结构 [96] ; (c) 硬质壳体增强的吸声结构 [94] , Copyright © 2022, Acoustic Society of America; (b) the hydroacoustic absorbing structure of the cylindrical cavity is enhanced by the aluminum cylinder [96] ; (c) hard shell enhanced hydroacoustic absorbing structure [97] 图 5 (网络版彩色)抗压吸声型水声超材料. (a) 含空腔和金属孔板 的超材料 [101] ; (b) 水声吸声超表面, 周期为A, 声波入射沿z轴负方 向 [102] .…”
Section: 吸声结构抗压设计mentioning
confidence: 99%
See 1 more Smart Citation
“…(a) Two-layer FGMs composite; (b) single-layer FGM is compounded with gradient cavities; (c) two-layer FGMs are compounded with gradient cavities 图 4 (网络版彩色)具有增强结构的抗压水声吸声结构. (a) 含钢隔 板增强结构的吸声材料在4.5 MPa下x方向的位移场图 [94] , Copyright © 2022, Acoustic Society of America; (b) 通过铝制圆筒增强柱形空 腔抗压性能的吸声结构 [96] ; (c) 硬质壳体增强的吸声结构 [94] , Copyright © 2022, Acoustic Society of America; (b) the hydroacoustic absorbing structure of the cylindrical cavity is enhanced by the aluminum cylinder [96] ; (c) hard shell enhanced hydroacoustic absorbing structure [97] 图 5 (网络版彩色)抗压吸声型水声超材料. (a) 含空腔和金属孔板 的超材料 [101] ; (b) 水声吸声超表面, 周期为A, 声波入射沿z轴负方 向 [102] .…”
Section: 吸声结构抗压设计mentioning
confidence: 99%
“…Figure 4 (Color online) Pressure-resistant hydroacoustic absorbing structure with reinforced structures. (a) Displacement field diagram of the hydroacoustic absorbing material with steel diaphragm reinforced structures at 4.5 MPa in the x direction[94] , Copyright © 2022, Acoustic Society of America; (b) the hydroacoustic absorbing structure of the cylindrical cavity is enhanced by the aluminum cylinder[96] ; (c) hard shell enhanced hydroacoustic absorbing structure…”
mentioning
confidence: 99%
“…On the other hand, the deformation of the rubber and cavity caused by hydrostatic pressure can be effectively reduced by supporting the metal wall connected to the backing, thereby enhancing the strength of the structure. Yang et al (2022b) revealed that the addition of aluminum hollow cylindrical supports around the cylindrical cavity not only effectively improved the hydrostatic pressure resistance performance of the structure but also enriched the sound absorption mechanism of the structure and enhanced the sound absorption performance under hydrostatic pressure. Li et al (2023) enhanced the structural strength by designing an underwater acoustic structure containing a rubber sandwich with a funnel-shaped cavity and adding carbon fiber columns as reinforcement materials.…”
Section: Design Of Acoustic Structures Resistant To Hydrostatic Pressurementioning
confidence: 99%
“…2 Underwater sound absorption is mainly comprised of passive sound absorption, active sound absorption, and semiactive sound absorption. Passive sound absorption uses viscoelastic materials with a cavity structure, [3][4][5] rigid inclusions, or scatterers 6 as the sound-absorbing material and reduces or eliminates the reflection of incident sound waves through energy attenuation. The sound absorption performance of passive sound absorption is good within the middle and high fre-quency band but is limited within the low frequency band.…”
Section: Introductionmentioning
confidence: 99%